Physico-chemical composition and antimicrobial protein content of early lactation donkey milk - Ioannou, Christina A.; Papademas, Photis; Souroullas, Kallis; Aspri, Maria (My University, 2019)
The in uence of early lactation on chemical composition and the concentration of antimicrobial proteins of donkey's milk produced in Cyprus were investigated. Milk samples from 10 female donkeys in their first season of lactation were collected at 7, 15 and 30d postpartum. The average contents of donkey milk gross composition were 1.40% protein, 0.16% fat and 8.74% total solids. Results showed that lactation had a significant negative effect on protein concentration, while total solid concentration showed an increased followed by a decrease. Composition of antimicrobial proteins also showed a significant decreased during lactation period except from lactoferrin which showed an increase. On the other hand, throughout the lactation, pH and fat were constant.
Keywords: Antimicrobial proteins; Donkey milk; Immunoglobulin-A; Lactation